The experimental study on pyrolysis of the cassava rhizome in the large scale metal kiln using flue gas - Homchat K. (2017)
The pyrolysis characteristics of the cassava rhizome in the large scale metal kiln using flue gas have been studied experimentally. The effect of inclined metal kiln of 0.57 m 3 was also considered. It was found that at 70 degree of incline angle of the metal kiln, the pyrolysis time was shortest due to the good temperature distribution throughout the kiln. At 70 degree of incline angle of the kiln, the pyrolysis time of the dry cassava rhizome was 95 minutes, while the fresh one was longer owing to more moisture content. The pyrolysis temperature distribution throughout the kiln of the flesh cassava rhizome was poor due to the high shrinkage of fresh one. The charcoal yield obtained from the dry cassava rhizome (11.22% moisture content) is 25-28% (db), while the charcoal yield from the fresh cassava rhizome (35.5% moisture content) is 35.65%(db) which is higher than that of the dry one due to effect of moisture content. © 2011 Published by Elsevier Ltd.